Pengaruh Variasi Temperatur Terhadap Kinetika Reaksi Solidifikasi Fly Ash Paving Blok Geopolimer - Aman Aman; Amir Awaluddin; Adrianto Ahmad; Monita Olivia (Dinamika Lingkungan Indonesia, 2018)
This paper reported about  the investigated of  fly ash solidification with geopolymer process that studied temperature variation on the rate of solidification using Vicat Nidle apparatus and leaching tests on the content of heavy metals Cu, Pb, Cr and Cd in paving blocks after solidification. The transformation process of geopolymer crystalline formation was analyzed by Avrami’s kinetics theory (Avrami’s kinetica theory). From the results of the study obtained the optimum temperature of 80 oC, the highest rate of crystal growth solidification (K) value of 0.0475 and the Avrami exponent value (n) of 2.310 in this geopolymerization process shows a two-dimensional structure. From the results of leaching levels of heavy metals Cu, Pb, Cr and Cd in fly ash paving blocks are very small degraded in water and still below the environmental threshold.